Enkulturasi Nilai-Nilai “Keislaman” dalam Proses Pembelajaran di TK Wihdatul Ummah Kota Makassar - Juwanita Sahid (Universitas Muslim Maros, 2020)
Early childhood education (PAUD) is a social institution that serves to instill cultural, national, and religious values in children. While the existing literatures on PAUD are more focused on the role of social institutions and formal educational institutions in the formation of children (school environment, learning process and community supporting the process), this article focuses on the process of enculturation in applying